Tax Holiday Regulations on Car Trade-in Indonesia: Between 2021-2022 - Muhammad Raihan Faqih; Fadlil Abdani (Universitas Negeri Surabaya, 2023)
This research was conducted by comparing the 2021 and 2022 PPnBM incentives to the total sales of motorized vehicles on a wholesale basis. The data used is of secondary data type and is sourced from the official website of the Association of Automotive Industries (GAIKINDO). The population in this study are automotive manufacturers who are members of GAIKINDO and for the sample in this study are 16 types or models of cars that receive 2021 and 2022 PPnBM incentive relief. The data collection process in this study uses a purposive sampling technique because the data used must meet some criteria. Hypothesis testing was carried out by using descriptive statistical tests, normality tests, homogeneity tests and paired sample t tests. The results of the paired sample t test show the value of Sig. (2-tailed) 0.008 which is < 0.05. So it can be interpreted that the 2022 PPnBM incentives are more influential or more effective on wholesale sales of motorized vehicles